Development and Implementation of E-Leave Management System in Banking Sector (KCB) - Owiti, shadrack Ochieng (JOOUST, 2015)
The research investigated the state of leave management system used by different organizations i.e. brief comparison of manual le-ave management system and E-leave management system. A leave management system had been deployed by Kenya Commercial Bank (KCB) IT department as a project but it had major drawbacks for example staffs could only apply for leave while within the bank intranet platform hence there was need to develop and deploy a multi platform leave management system. A huge proportion of KCB staff had been manually applying for leave due to inadequate IT skills, insufficient leave application platforms and resistance to change hence there was need to develop multi platform leave management system with a simplified one paged leave application form. The current leave system lack reminders therefore not efficient and supports limited number of employees and is subjective to errors hence the need to develop multi platform leave management system. The discussion then focused on the advantages and the limitations of E-leave management system as compared to manual leave management system with a critical look at performance. The performance of E¬leave management system was examined in relation to six main criteria; ability to enable staffs easily apply for leave online, ability to enable managers receive online leave application from staffs, ability to approve or reject staff leave application automatically, ability to easily help in identification of leave balance from affix amount of total leave days, ability to record all leave information in the database and ability to generate reports based on staffs leave. Data was collected by use of interviews that targeted an managers in the branch, questionnaires that collected views from a sample of forty four staff members and focus group discussions was used to get in-depth views of IT expects in the bank. For the development of the platform software development life cycle and database life cycle were used as methodologies. The E-leave management system developed in this project has fully automated leave management process and can be implemented in any platform. Further research on cheaper methods of sending sms i.e. the use of P1aysms and kannel gateway which only cost k:sh. 0.40 as compared to current charge proposed by the project which cost k:sh.1.00. Playsms works best if 1inux operating system and involes the use of safaricom modem and also requires coding using python so that the modem sends/ receives sms.